Ecofeminist Perspective in International Relations Study: #IAmWiSER Campaign Study at COP27 - Asriasni, Rini (Global Writing Academica Researching & Publishing, 2024)
This study aims to investigate the ecofeminist movement as manifested in the #IAmWiSER campaign at COP27 in Egypt, with the objective of advocating for gender and environmental concerns within the realm of global politics. It seeks to delve into the ecofeminist perspective embodied in the #IAmWiSER campaign at COP27 in Egypt and aims to elucidate the ecofeminist movement undertaken by female delegates representing nations and international organizations through their participation in the #IAmWiSER campaign. Furthermore, the research endeavors to delineate the ecofeminist movement within the #IAmWiSER campaign by examining how ecofeminist movements and perspectives can unveil the ways in which international control and authority may jeopardize planetary security, particularly through the lenses of patriarchy, capitalism, anthropocentrism, dichotomies, and exploitation. Methodologically, this study adopts descriptive-explanatory approaches utilizing data from the #IAmWiSER campaign available on the official Masdar platform, supplemented by relevant literature. It is anticipated that the findings of this research will yield novel insights into the interconnectedness of nature and humanity, highlighting the repercussions of environmental exploitation on women and girls. Consequently, policies concerning women and the environment should be crafted with due consideration to gender and ecological perspectives.